Of land use mix, location and travel carbon emission: state of the relationship in neighbourhoods of Iskandar Malaysia - Wan Kassim, Sharifah Athirah Izyan (2014)
Climate has been changing due to increasing level of greenhouse (GHG) emission from human activities and land use has been identified as one of the major factors. The increasing rate of urbanisation with its sprawl consequences has long been a concern in terms of major source of CO2 emission. Land uses in terms of types, amount and location do have direct and indirect effects on CO2 emission. Aim of this research is to identify the optimal mix and siting of land uses in neighborhoods in Iskandar Malaysia based on the physical layouts of existing neighborhoods. In line with the goal of Iskandar Malaysia to be the first Low Carbon City in Malaysia, this research might help by providing the information needed in order to achieve it. Iskandar Malaysia is chosen for this research because in Iskandar Malaysia it already have three types of mixed uses category but yet no one have measure the level of this mixed use development. This research have selected for about ten neighborhoods developed from 1980s to 2000s ranging from 100-1000 acres as it sample. Assessment and analysis are carried out on several metrics to investigate the relationship between land use mixing, location of land uses and travel carbon emission. CommunityViz an ArcGIS based on scenario planning softwares, is used to compare the impact of various real and hypothetical land use mix scenarios on internal travel and eventually travel carbon emission. The findings seem to indicate that the mixing as well as the location of land uses do affect travel carbon emission greatly. Travel carbon emission is worse in exclusive neighborhoods that cater only for residential uses.